2007
DOI: 10.21091/mppa.2007.1004
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Analysis of Hand and Finger Movements during Piano Playing

Abstract: The movements required for piano playing usually involve low impact loads that do not exceed physiologic limits of human body, but their repetition may provoke microtrauma leading to overuse injuries. Experience may allow a pianist to modify the motor patterns used for a performance, allowing the highest accuracy with minimum effort. In the present study, hand and finger movement patterns were analyzed in 19 pianists (8 concert players, 11 students and teachers) while they played 16 measures of a minuet. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Systems can be split into either passive (paint or reflective markers used, or markerless systems) or active (devices which require power whether that be by battery or via cable to a power supply). Motion capture is a common type of passive system used to examine the upper body or hand/finger movement of the performer: examples of these are depth camera tracking using the Kinect system (Hadjakos, 2012); image motion capture with paint markers (MacRitchie & Bailey, 2013); infrared motion capture using reflective markers attached to the skin or body (Dalla Bella & Palmer, 2006, 2011; Ferrario, Macri, Biffi, Pollice & Sforza, 2007; Furuya, Goda, Katayose, Miwa & Nagata, 2011; Goebl & Palmer, 2008, 2013; Sakai, Liu, Su, Bishop & An, 2006). Active devices can be categorised into two groups: the first which are generally attached to the performer (LED position sensors - Furuya & Kinoshita, 2007; accelerometers - Hadjakos, Aitenbichler & Mühlhäuser, 2008; Rahman, Mitobe, Suzuki, Takano & Yoshimura, 2011; Grosshauser, Tessendorf, Tröster, Hildebrandt & Candia, 2012; data glove - Furuya, Flanders & Soechting, 2011; Furuya & Soechting, 2012; electrogonimoters - Chung, Ryu, Ohnishi, Rowen & Headrich, 1992), the second which are attached to, or form part of, the instrument in order to measure the tangible results of such touch techniques (key-angle - McPherson & Kim, 2011; Bernays & Traube, 2012; location of finger-key contact - Moog & Rhea, 1990; McPherson, 2012; force transducers - Parlitz, Peschel & Altenmüller, 1998; Kinoshita, Furuya, Aoki & Altenmüller, 2007; force and torque sensors - Grosshauser, Tessendorf, Tröster, Hildebrandt & Candia, 2012).…”
Section: Measurement Techniques For Touch In Piano Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Systems can be split into either passive (paint or reflective markers used, or markerless systems) or active (devices which require power whether that be by battery or via cable to a power supply). Motion capture is a common type of passive system used to examine the upper body or hand/finger movement of the performer: examples of these are depth camera tracking using the Kinect system (Hadjakos, 2012); image motion capture with paint markers (MacRitchie & Bailey, 2013); infrared motion capture using reflective markers attached to the skin or body (Dalla Bella & Palmer, 2006, 2011; Ferrario, Macri, Biffi, Pollice & Sforza, 2007; Furuya, Goda, Katayose, Miwa & Nagata, 2011; Goebl & Palmer, 2008, 2013; Sakai, Liu, Su, Bishop & An, 2006). Active devices can be categorised into two groups: the first which are generally attached to the performer (LED position sensors - Furuya & Kinoshita, 2007; accelerometers - Hadjakos, Aitenbichler & Mühlhäuser, 2008; Rahman, Mitobe, Suzuki, Takano & Yoshimura, 2011; Grosshauser, Tessendorf, Tröster, Hildebrandt & Candia, 2012; data glove - Furuya, Flanders & Soechting, 2011; Furuya & Soechting, 2012; electrogonimoters - Chung, Ryu, Ohnishi, Rowen & Headrich, 1992), the second which are attached to, or form part of, the instrument in order to measure the tangible results of such touch techniques (key-angle - McPherson & Kim, 2011; Bernays & Traube, 2012; location of finger-key contact - Moog & Rhea, 1990; McPherson, 2012; force transducers - Parlitz, Peschel & Altenmüller, 1998; Kinoshita, Furuya, Aoki & Altenmüller, 2007; force and torque sensors - Grosshauser, Tessendorf, Tröster, Hildebrandt & Candia, 2012).…”
Section: Measurement Techniques For Touch In Piano Performancementioning
confidence: 99%
“…Studies measuring 19 pianists’ hand movements in a musical excerpt found differences between the professionals and the students and teachers in terms of the total kinetic energy used. (Ferrario et al, 2007). This study attempted to separate the movements necessary for the keypress from extraneous movements which could lead to injury, finding that the professionals had a greater amount of ‘useful’ kinetic energy per keypress than the students and teachers.…”
Section: The Keypress - Acoustic and Biomechanical Studiesmentioning
confidence: 99%
“…Typically, the teaching and correction of finger technique for piano beginners are guided by music teachers, incurring high labor costs, and it's challenging for beginners to consistently maintain the correct finger technique. With the development of exoskeleton technology, hand-assist exoskeletons are increasingly applied in the field of piano learning and performance [7,8]. Cai Rongjie et al utilized Leap Motion to establish a fingertouch action measurement platform, collecting parameters of finger-touch actions and obtaining the movement curve of finger-playing keys.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on kinematic studies of pianists is still insufficient, and there is a lack of strong evidence and rationale to address the importance of the relationship between kinematics and piano-playing-related injuries. Only a few studies have investigated hand postures and finger movements of pianists while playing assigned musical compositions using electrogoniometers, camcorders, or three-dimensional motion capture systems [20][21][22][23][24][25][26][27]. Lee examined the relationships between anthropometry and kinematics, such as the hand length, hand width, finger length, active finger span, wrist ulnar deviation, and hand weight, with the performance of a scale in thirds [28].…”
Section: Introductionmentioning
confidence: 99%